A method to measure the insitu magnetic field in a Hall thruster based on the Faraday rotation effect. (8th May 2019) - HAN 韩, Liang 亮; GAO 高, Jun 俊; CHEN 陈, Tao 涛; CONG 丛, Yuntian 云天; LI 李, Zongliang 宗良
Abstract: This paper presents a method to measure the in situ magnetic field in a Hall thruster by optical non-invasive means, based on the optical Faraday rotation effect. This method does not affect the discharge of the thruster. Furthermore, its time resolution depends on the speed of the photo-detector, and measurement at a MHz scale can be achieved.